The Factors Influencing the Satisfaction Level of the Communities Residing in Gated Housing Schemes in Klang Valley - Zainab Abdul Latiff (Journal of Architecture, Planning and Construction Management, 2020)
This study aims to evaluate the factors influencing the satisfaction level of the community residing in gated housing schemes in Klang Valley. The measuring variables are 1) security, 2) privacy, 3) lifestyle, 4) location, 5) investment and 6) demographic background. This study was conducted in thirteen different gated housing schemes through convenience random sampling of 170 heads of households staying in Klang Valley via a questionnaire survey which consists of multiple choice questions and a 5-point likert scale. Two main hypotheses were tested using Pearson Correlation, Independent sample t-test, ANOVA and Chi square tests. The study revealed four important findings: 1) only ‘number of household’ influences the satisfaction level of living in gated housing schemes; 2) privacy is the leading factor influencing house buyers; 3) the management board has no effect on satisfaction level and; 4) those staying in gated housing schemes socialise moderately. Overall, it shows that the study areas conform to the definition of gated housing schemes formulated by the Federal Town and Country Planning Department (2010). Therefore, in order to enhance social interaction among gated housing schemes, existing developments with neighbourhood unit features need to consistently produce face-to-face social conditions through the provision of multipurpose hall, musolla, playground and the likes. Next, local authorities, developers and residents’ association can take advantage of the multi-ethnic and cultural scenario of the gated housing schemes by organising resourceful activities such as ‘eyes on the street’ and neighbourhood watch programs which would indirectly improve the security of the neighbourhood. Lastly, organising residents’ association meeting once a month is very important to the residents since they work long hours thus, explain why they emphasise more on spending their leisure time with their family whenever they are free, rather than building relationship with neighbours.